A unique three-way Philadelphia chromosome variant t(4;9;22)(q21;q34;q11.2) in a newly diagnosed patient with chronic phase chronic myeloid leukemia: a case report and review of the literature - Torii, Yuka (J Med Case Rep, 2021)
BACKGROUND: Chronic myeloid leukemia is a hematologic malignancy associated with the fusion of two genes: BCR and ABL1. This fusion results from a translocation between chromosomes 9 and 22, which is called the Philadelphia chromosome. Although the Philadelphia chromosome is present in more than 90% of patients with chronic myeloid leukemia, 5–8% of patients with chronic myeloid leukemia show complex variant translocations. Herein, we report a unique case of a three-way translocation variant in chronic phase chronic myeloid leukemia. CASE PRESENTATION: A 40-year-old Asian male who presented with leukocytosis was diagnosed with chronic phase chronic myeloid leukemia. Cytogenetic karyotyping analysis showed 46,XY,t(4;9;22)(q21;q34;q11.2). He was treated with bosutinib and then changed to dasatinib because of intolerance, and MR4.5 (BCR-ABL/ABL ≦ 0.0032%, international scale) was achieved after 17 months of continuous treatment. CONCLUSION: This was the 14th case of t(4;9;22), in particular, a new variant Ph translocation involved in chromosome 4q21 and the first successful case treated with tyrosine kinase inhibitors in the world. We summarize previous case reports regarding three-way variant chromosome translocation, t(4;9;22) and discuss how this rare translocation is linked to prognosis.